Optimization of Self Monitoring Blood Glucose in Diabetes Mellitus Patients in Detecting Hypoglicemia Episodes: Literature Review - Ninik Ambar Sari; Ceria Nurhayati (Universitas Airlangga, 2021)
Introduction: Diabetes mellitus is a chronic disease that continues to increase from year to year. The act of detecting hypoglycemic episodes is a must for a diabetic patient. This study aims to present the optimization of blood glucose self-monitoring measures in patients with diabetes mellitus and to review some of the literature on this topic.Methods: This study is a form of literature review of articles with the theme Optimization Self Monitoring Blood Glucose in diabetes mellitus patient detecting hypoglicemia episodes. Articles in this study came from the electronic databases of Google Scholar, PubMed, Proquest, Scopus and Science Direct from 2005 to 2020. Results: Search results using the keywords Self Management Blood Glucose, Hypoglicemia, Diabetes Mellitus were obtained from 57 articles. 18 articles that met the inclusion criteria were then reviewed for their full text. Conclusion: Self Monitoring Blood Glucose is a preventive measure in detecting hypoglycemic episodes. This intervention is the best choice for patients to prevent further complications.